Parents Knowledge, attitude and practice of antibiotic use for upper respiratory tract infections in children: a cross-sectional study in Ras Al khaimah, United Arab Emirates (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Upper respiratory tract infections are common in children and represent a significant cause of antibiotic abuse. Parents’ knowledge and attitudes often contribute to inappropriate prescription of antibiotics and promoting antibiotics resistance. The study aimed at exploring parental knowledge, attitudes and practices towards antibiotic use in children with URTI along with identifying the reasons behind self-medication and abuse of antibioticsMethods: A cross sectional survey was conducted at pediatric outpatient clinics of Saqr Hospital in the emirate of Ras Al Khaimah,United Arab Emirates A structured interview questionnaire was used to collect data from 239 parents of children aged less than7 years, between February to March 2016Results: More than half (54.4%) of the respondents had a poor level of knowledge. About (66.1%) were not aware that antibiotics are indicated to treat bacterial infection. However, 67.2 % of the respondents incorrectly identified that antibiotics are used to treat viral infections. Nearly 44.5 % of the respondents were aware of antibiotic resistance in relation to its overuse. With regard to attitude, 68.2% of the respondents believed that they would be satisfied if physicians did not prescribe antibiotics for common cold. Yet, 63% would request it if physicians did not prescribefor frequent URTIs. Nearly 43.5% of respondents gave self-medication to their children mostly because of repeated similar attacks and over the counter acquisition of antibiotics. Most (82.2%) of them declared that, physicians did not provide sufficient information regarding diagnosis and therapy More than half (54.4%) of the respondents had a poor level of knowledge. About (66.1%) were not aware that antibiotics are indicated to treat bacterial infection. However, 67.2 % of the respondents incorrectly identified that antibiotics are used to treat viral infections. Nearly 44.5 % of the respondents were aware of antibiotic resistance in relation to its overuse. With regard to attitude, 68.2% of the respondents believed that they would be satisfied if physicians did not prescribe antibiotics for common cold. Yet, 63% would request it if physicians did not prescribe for frequent URTIs. Nearly 43.5% of respondents gave selfmedicationto their children mostly because of repeated similar attacks and over the counter acquisition of antibiotics. Most (82.2%) of them declared that, physicians did not provide sufficient information regarding diagnosis and therapyConclusions: Educational programs are needed to raise awareness and correct expectations about judicious use of antibiotics